Who Are the Value and Growth Investors? - BETERMIER, SEBASTIEN; CALVET, LAURENT E.; SODINI, PAOLO (Journal of Finance, 2017)
ABSTRACT This paper investigates value and growth investing in a large administrative panel of Swedish residents. We show that, over the life cycle, households progressively shift from growth to value as they become older and their balance sheets improve. Furthermore, investors with high human capital and high exposure to macroeconomic risk tilt their portfolios away from value. While several behavioral biases seem evident in the data, the patterns we uncover are overall remarkably consistent with the portfolio implications of risk‐based theories of the value premium.